Laparoscopic Vs Open Surgery for Colorectal Cancer: Comparing Short-Term Results - Zakir Ahmad Khan, Ajmal Khan, Muhammad Bilawal Khan, Kamran Khan, Muhammad Waqas Khan, Karishma Rehman, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In developed countries, colorectal cancer continues to rank as the third-most prevalent cancer to be reported and the third-most popular reason for cancer mortality in both genders. Objective: The purpose of the retrospective research was to compare the operational parameters and short-term oncological effects of laparoscopic surgery (LS) with traditional open surgery (OS) in colorectal cancer patients in our hospital. Methods: In this study, 148 patients who underwent CRC surgery between January 2020 and January 2022 at the Medical Teaching Institute (MTI) Peshawar, Pakistan's Khyber Teaching Hospital and Hayatabad Medical Complex Hospital were included. 64 people who had all had LS were included in the study. On the other hand, 84 people who had had OS were randomly selected from groups of people who were of the same gender and age. Result: In the group undergoing OS, the median of dissected lymph nodes was 22.8 (9–35) and 3 (0–14), whereas, in the group undergoing laparoscopy, the median number was 21.56 (8–32) and 6.2 (0–9). For 13 (15.47%) patients undergone through and 9 patients (14.06%) undergone through laparoscopy, blood transfusions were necessary. Although the LS group's procedure took longer than the OS group, their time in the ICU, time to start feeding and duration of stay at the hospital were all shorter. Practical implication Importance Laparoscopic surgery has not been proven to be more effective than open surgery for patients with low rectal cancer. Conclusion: LS provides the benefits of a shorter hospital stay and fewer problems and delivers relatively adequate lymph node dissection. Keywords: laparoscopic surgery, open surgery, colorectal cancer, oncological outcomes, developing countries